(untitled) (Journal for Freedom of Conscience (Jurnalul Libertății de Conștiință), 2022)
Human Liberty as an Expression of the Protestant Ethos at William James William James is one of the most prominent philosophers of the late nineteenth century and early twentieth century in America. He has come to be known for his theory of pragmatism. But one of his major themes is, human freedom. In this paper I will take in consideration his view on freedom, based on three major treatises of his works: The Will to Believe, Pragmatism and A Pluralistic Universe. I will conclude with a correlation between his view on freedom and the Protestant ethics, specific to the Reformed societies, stated by Max Webber.